DYNAMICS OF ENTREPRENEUR ARCHIVALISTS OF GOVERNMENTAL ORGANIZATIONS - Silaban, Krisdayanti; Yuni K, Kusnul Ciptanila (Universitas Terbuka, 2024)
This study aims to examine the management of dynamic records in the General Affairs section of Humbang Hasundutan Regency. The research method used is qualitative with a descriptive approach, which seeks to analyze the current state of dynamic records management, identify challenges encountered, and provide recommendations to enhance the efficiency of this management. Data collection techniques included observation, interviews, and document studies. The results of this study indicate that the management of dynamic records in the General Affairs section of the Regional Secretariat of Humbang Hasundutan Regency is still not optimal, requiring comprehensive and integrated actions, such as formulating clear dynamic records management policies and implementing them with discipline. Additionally, the adoption of an electronic records management system and training for relevant staff are also important steps in improving the optimization of dynamic records management.